Ideological perspectives in the Persian translations of animal farm and nineteen eighty-four / Amin Amirdabbaghian - Amin , Amirdabbaghian (2019)
The ideology and worldviews of a community can be subject to shifts and modifications through social changes brought about by political upheavals. In a country like Iran, the Islamic Revolution (1979/80) has played a major role in re-shaping the ideology of the governing body which among many other things involves modifications in the language policy. After the Revolution, Persian speakers were encouraged to be more conservative in their use of language. As a result, those who tended to produce discourse which was more conservative and Islam-oriented became more popular and respected among the Iranian people. Ideology is one of the major factors which influences the manipulation of language use in translation. This study aims to describe the ideological impact of the social situation both in the pre- and post-Revolution era in Iran on translations of George Orwell’s famous political novels, Animal Farm (1945) and Nineteen Eighty-Four (1949) into Persian. This study will, therefore, compare two Persian translations of both novels which were produced before and after the 1979 Iranian Islamic Revolution. Farahzad’s (2012) three-dimensional translation criticism model, which comprises textual, paratextual and semiotic levels, has been employed to categorize the samples. Van Dijk’s (1998) theory of ideology is used to discuss the samples in the textual part while Lefevere’s (1992a) theory of translation, rewriting and manipulation of literary fame has been applied to discuss the paratextual differences between the pre- and post_Revolution Persian translations of the novels. Finally, for the discussions on the semiotic part of the corpus which involves front covers of the original and translated novels, Serafini’s and Clausen’s (2012) model of typography for the semiotic resource as well as Kress and Van Leeuwen’s (2006) model of semiotic analysis are used.